Preparation of micro-calcite powder using fine-bubble assisted carbonation as toothpaste material - Febrida, Renny; Nabillah Salma, Dinda Jihan; Azzahra, Fauziah; Karlina, Elin; Andiesta, Niekla Survia; Faza, Yanwar (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Calcite (CaCO3) is typically used in commercial toothpaste with particle size ranges from 1-12 μm. In the latest study, calcite was synthesized by using Ca(OH)2 precursor from natural resources However, the resulting particle size does not match the size of the toothpaste filler. This study aims to prepare micro-calcite via fine-bubble assisted carbonation as toothpaste material. Methods: The calcite powder was prepared from Ca(OH)2 analytical grade powder utilizing the fine-bubble carbonation process with the Ca(OH)2 concentration and initial pH variation. The study was started by making a Ca(OH)2 suspension with a concentration of 0.25, 0.5, 0.75, 1 and 1.25 M using 2.000 ml methanol as a solvent. 0.5 M NaH2PO4 solutions were utilized to adjust the initial pH of 0.5 M Ca(OH)2 suspension into 8, 9, and 10. The suspensions were aerated using CO2 fine-bubble for two hours to produce CaCO3 samples. All precipitated CaCO3 particles were characterized by PSA, Zeta-Potential, and FTIR measurements. Results: The calcite phase was identified from the FTIR transmittance. Aragonite or vaterite phase was not observed in the samples. PSA result shows the size of CaCO3 particles from samples 0.25 M to 1.25 M are as follows 3.03, 3.23, 2.79, 3.70, 0.99 μm respectively. Meanwhile, the particle sizes of CaCO3 in samples with a pH of 8, 9 and 10 are 3.00, 2.03 and 2.50 μm respectively. The zeta potential shows the value ranges from -23.2 mV to -11.9 mV, indicating fair dispersion ability. Conclusion: The fine bubble assisted carbonation method in this study helps in producing calcite in micron size that could be used as alternative fillers for toothpaste.Keywords: calcite, fine-bubble, carbonation, particle size, toothpaste